Effect of a nursing care program based on Roy\'s adaptation model on sleep quality in patients undergoing methadone maintenance treatment: A randomized clinical trial - Amir Musarezaie; Soheila Pezeshkzad; Sayyed Abbas Hosseini; Mohammad Javad Tarrahi; Meysam Rezazadeh (Tehran University of Medical Sciences, 2024)
Background & Aim: The misuse of opioids is one of the most important problems in today's world, directly affecting the quality sleep for individuals. This study sought to explore the effect of a nursing care program, based on Roy's adaptation model, on the sleep quality of patients undergoing methadone maintenance treatment. Methods & Materials: This randomized, single-blind clinical trial was conducted between December 2022 and March 2023, involving 60 opioid abuse patients undergoing methadone maintenance treatment at the Addiction Reduction Center in Isfahan. Convenience sampling was employed, with participants allocated randomly using random sequence generation software into the intervention group (n=30) and the control group (n=30). Data was collected using the Pittsburgh Sleep Quality Questionnaire. The intervention comprised a three-month nursing care program based on Roy's adaptation model, while the control group received routine treatments. Data analysis was performed using SPSS version 26 software, utilizing descriptive and inferential statistics. Results: The results showed a significant decrease in the total average score of sleep quality in the intervention group after the intervention, indicating an improvement in sleep quality (P<0.001). Before the intervention, there was no statistically significant difference in the total average score of sleep quality between the intervention and control groups (P>0.05); however, a significant difference was observed after the intervention (P<0.001). Conclusion: The findings indicate that the nursing care program based on Roy's adaptation model is effective in improving the sleep quality of patients undergoing methadone maintenance treatment. Therefore, this model can provide a promising framework for delivering care to such patients. Clinical trial registry: IRCT20141127020108N6